The competence profile of lecturers in didactics of Physical Education in Switzerland - Christelle Hayoz (Bern Open Publishing, 2023)
Since the introduction of the Higher Education Promotion and Coordination Act (HEdA), Swiss universities of teacher education (UTE) had to offer continuing education, additional training, teaching, research and development (Staatssekretariat für Bildung, Forschung und Innovation, 2021). This mandate led to a dual competence requirement of teaching and research for lecturers (Freisler-Mühlemann, 2020; Sibold, 2017). The current state of research shows that there is a need for clarification regarding the dual competence profile of lecturers at Universities of Teacher Education (swissuniversities, 2021). In order to answer the question of how these competence requirements are perceived by lecturers, the subjective perceptions of a total of 18 sports didactics lecturers from eight different UTE in German- and French-speaking Switzerland were collected by means of semi-structured qualitative guided interviews. The qualitative content analysis according to Mayring (2015) showed that the competence requirements are perceived differently and that various competence profiles exist. A valuable contribution could be made to the (dual) competence profile of sports didactics lecturers as well as to the promotion of sports didactics as a scientific discipline. References Freisler-Mühlemann, D. (2020). Doppeltes Kompetenzprofil - Leitvorstellungen an das Personal von Pädagogischen Hochschulen? [Double competence profile - Guiding principles for the staff of teacher training colleges?]. In A. Tettenborn & P. Tremp (Eds.), Pädagogische Hochschulen in ihrer Entwicklung und Berufsbezug. Hochschulkulturen im Spannungsfeld von Wissenschaftsorientierung (pp. 65-66). Pädagogische Hochschule Luzern. Mayring, P. (2015). Qualitative Inhaltsanalyse. Grundlagen und Techniken [Qualitative content analysis. Basics and techniques] (Beltz Pädagogik, 12th rev. ed.). Beltz. Sibold, N. (2017). Nachwuchsförderung an Schweizer Fachhochschulen und Universitäten - Entwicklungen, Positionen und Herausforderungen [Promotion of young researchers at Swiss universities of applied sciences and universities - Developments, positions and challenges]. In L. Truniger (Ed.), Führen in Hochschulen. Anregungen und Reflexionen aus Wissenschaft und Praxis (pp. 105-122). Springer Gabler. Staatssekretariat für Bildung, Forschung und Innovation. (2021). Fachhochschulen und pädagogische Hochschulen [Universities of applied sciences and teacher training colleges]. https://www.sbfi.admin.ch/sbfi/de/home/hs/hochschulen/kantonale-hochschulen/fh-ph.html Swissuniversities. (2021). P-11 Doppeltes Kompetenzprofil [P-11 Double competence profile]. https://www.swissuniversities.ch/themen/nachwuchsfoerderung/p-11-doppeltes-kompetenzprofil